2014
DOI: 10.1063/1.4894445
|View full text |Cite
|
Sign up to set email alerts
|

Probing the structural dependency of photoinduced properties of colloidal quantum dots using metal-oxide photo-active substrates

Abstract: We used photoactive substrates consisting of about 1 nm coating of a metal oxide on glass substrates to investigate the impact of the structures of colloidal quantum dots on their photophysical and photochemical properties. We showed during irradiation these substrates can interact uniquely with such quantum dots, inducing distinct forms of photo-induced processes when they have different cores, shells, or ligands. In particular, our results showed that for certain types of core-shell quantum dot structures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 47 publications
(68 reference statements)
0
26
0
Order By: Relevance
“…This is consistent with our previous investigations that showed the impact of Al oxide is very dependent on the type of the substrate and the QDs. 23,24 For types of QDs that exhibit active photo-chemical and photo-physical properties, Al oxide can lead to a significant amount of enhancement of emission efficiency of the QDs. We believe the reason behind the results seen in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with our previous investigations that showed the impact of Al oxide is very dependent on the type of the substrate and the QDs. 23,24 For types of QDs that exhibit active photo-chemical and photo-physical properties, Al oxide can lead to a significant amount of enhancement of emission efficiency of the QDs. We believe the reason behind the results seen in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the Al oxide passivated the amorphous Si layer by reducing defect sites, and also prevented the QDs from losing electrons to the Si layer by electrostatic shielding via its large and negative fixed potential. 23,24 These properties of Al oxide, combined with the high-index advantages of Si, seemed to be major factors in the significant enhancement of the QDs in NR-QD systems. Further studies on this topic are required to understand how one can use the unique properties of the Si/Al oxide interface to significantly enhance excitonplasmon coupling in such systems.…”
Section: Introductionmentioning
confidence: 99%
“…These include rigorous structural passivation, increase in the thicknesses of the QD shells, irradiation (photoinduced fluorescence enhancement), and field‐induced passivation. [ 8–14 ] They also include application of near fields of localized surface plasmon resonances (LSPRs). Here the main goal is to enhance the spontaneous emission decay rate of QDs using plasmon near fields (Purcell effect).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, it was shown that CdSe QDs can undergo a significant fluorescence enhancement when they are deposited on a silicon (Si) substrate coated with an ultrathin layer of aluminum (Al) oxide and irradiated for a period of time. 11,12 In this process, also called photo-induced fluorescence enhancement (PFE), the Al oxide acted as a "catalyst" layer; it enhanced the quantum efficiency of the QDs via passivation of the defect sites of the QDs and the Si substrate and simultaneously balanced the impact of the Si substrate. 11 Other recent reports have shown that, depending on the types of the QDs, chromium (Cr) oxide can lead to catalytic properties that differ from Al oxide.…”
mentioning
confidence: 99%
“…In fact, our previous reports have shown that Cr oxide may have some resemblance with Al oxide, but that the latter has a more pronounced enhancement effect. 12 This may be related to the fact that Al oxide can not only passivate the defects in QDs and on the Si substrate [15][16][17] but it can also isolate the QDs from the substrate because of its large negative fixed charge. 18 These negative charges induce electrostatic shielding between the QDs and the Si, preventing electrons from being ejected from the QDs, and residing in the Si layer.…”
mentioning
confidence: 99%